Measuring Health Literacy in Tuscany through the Italian risk factor surveillance system (PASSI). (30th September 2020) - Zanobini, P; Lorini, C; Caini, S; Lastrucci, V; Masocco, M; Minardi, V; Contoli, B; Bonaccorsi, G
Abstract: Background: Health literacy (HL) can be defined as the degree to which individuals have the capacity to obtain, process, and understand basic health information and services needed to make appropriate health decisions. A module to measure HL has been implemented in Tuscany since 2017 within the Italian risk factor surveillance system (PASSI). Here, we aimed to assess HL levels and their relations with social determinants and health behaviours. Methods: During 2017-2018, a representative sample (N > 7000, aged 18 to 69 years) of the Tuscan population was interviewed in PASSI. HL was measured using the Italian version of the short-short form (HLS-EU-Q6) of the HLS-EU-Q47. Multivariate analysis was performed to investigate associations between HL, social determinants and selected health behaviours (diet and physical activity). Results: 61% of the interviewees had an adequate HL level, 30% problematic and 9% inadequate. In the multivariate analysis, the odds of inadequate HL level increased for all social determinants except gender and loneliness. The strongest association was observed for foreign citizenship (OR 3.38, 95% CI 2.63-4.34) followed by financial problems (OR 2.10, 95% CI 1.73-2.55), low education (OR 1.91, 95% CI 1.58-2.32), being aged 50-69 years (OR 1.51, 95% CI 1.18-1.94) and unemployment (OR 1.42, 95% CI 1.17-1.72). With regard to health behaviours, subjects with inadequate HL level had the lowest odds of engaging in regular physical activity (OR 0.59, 95% CI 0.49-0.71) and one of the lowest odds of eating at least three portions of fruit and vegetables (OR 0.79, 95% CI 0.65-0.95). Conclusions: Our findings suggest that HL is strongly associated with social determinants and has major influence on health behaviours. Our study is still ongoing, with the next step being to build a conceptual model to depicting the effect of HL as a mediator of the association between social determinants and health behaviours. Key messages: Health Literacy is strongly associated with social determinants. Health Literacy has major influence on health behaviours.